2020
DOI: 10.20944/preprints202004.0347.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Chimeric Peptides to Block the SARS-CoV-2 Spike RBD

Abstract: Background: There are no known medicines or vaccines to control the COVID-19 pandemic caused by SARS-CoV-2 (nCoV). Antiviral peptides are superior to conventional drugs and may also be effective against COVID-19. Hence, we investigated the SARS-CoV-2 Spike RBD (nCoV-RBD) that interacts with hACE2 for viral attachment and entry. Methods: Three strategies and bioinformatics approaches were employed to design potential nCoV-RBD - hACE2 interaction-blocking peptides that may restrict viral attachment and entry. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…A 26 amino acid peptide (AC26) binds to Thr500 and Asn501 of the Spike RBD ( Figure 1A ), a 23 amino acid peptide (AC23) binds to Tyr489 and Thr500 of the Spike RBD ( Figure 1B ), and a third 20 amino acid peptide (AC20) binds to Gln493 and Asn501 of the Spike RBD ( Figure 1C ). All these peptides show acceptable physiochemical properties to be used as therapeutic peptides (see Extended data 26 ). However, none of these three peptides are able to block all the key three positions of the Spike RBD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A 26 amino acid peptide (AC26) binds to Thr500 and Asn501 of the Spike RBD ( Figure 1A ), a 23 amino acid peptide (AC23) binds to Tyr489 and Thr500 of the Spike RBD ( Figure 1B ), and a third 20 amino acid peptide (AC20) binds to Gln493 and Asn501 of the Spike RBD ( Figure 1C ). All these peptides show acceptable physiochemical properties to be used as therapeutic peptides (see Extended data 26 ). However, none of these three peptides are able to block all the key three positions of the Spike RBD.…”
Section: Resultsmentioning
confidence: 99%
“…In our peptide database analysis, we also observed that the peptides that have been experimentally proven to be effective against SARS-CoV have the potential of being used against the SARS-CoV-2 Spike protein. All of the seven identified peptides (see Extended data 26 ) are of 20 amino acids in length and are reported to target the Spike protein of SARS-CoV to exhibit their anti-SARS virus activities 19 . Although the peptides show four to 11 “H” bonds and form between two to four bonds with our eight given target residues, most of these peptides do not bind to all the three positions ((i) Gly485 or Phe486 or Asn487, (ii) Gln493, and (iii) Gln498 or Thr500 or Asn501) to effectively block the Spike RBD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proposed in the report, at least one peptide inhibitor was able to specifically bind to the spike protein and prevent SARS-CoV-2–RBD/ACE2 interactions. Barh et al [ 47 ] and Huang et al [ 48 ] also shared their initial computational findings in preprints posted on preprints and BioRxiv , respectively. Using bioinformatics strategies, Barh et al screened and designed several potential anti-S protein peptides that may limit viral attachment and entry.…”
Section: Investigations Of Peptide Inhibitors Targeting Spike–ace2 Inmentioning
confidence: 97%